Human Metapneumovirus Infection in Chimpanzees, United States - Owen M. Slater (Emerging Infectious Diseases, 2014)
Zoonotic disease transmission and infections are of particular concern for humans and closely related great apes. In 2009, an outbreak of human metapneumovirus infection was associated with the death of a captive chimpanzee in Chicago, Illinois, USA. Biosecurity and surveillance for this virus in captive great ape populations should be considered.